(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper studies the elements pertaining to formal education among the tribes of India and in particular to the students of Northern Andhra Pradesh. The study focuses on the reasons for drop out among tribal students due to various reasons and proposes initiatives to be taken to enhance the enrollment. The paper furnishes the drop out trends from 1995 to 2020 with regard to general population vis-à-vis tribal students.